(untitled) (REMUNOM, 2026)
This work aims to present a way to teach the geometry content of metric relations in right triangles using a grid as a resource. The bibliographic references used were Silva & Barbosa (2022), who pointed out the causes of difficulty in this content; Carvalho (2004), who pointed out difficulties and highlighted the importance of this content; Lamas & Mauri (2006), who used rubberized materials to teach this content; Santos & Mendonça (2016), who use robotics as a methodology for this content; and Pires (2018), who uses the GeoGebra software to teach this content. The methodology used to produce this text was qualitative research based on the work of other authors and our experience in teaching mathematics as teachers. As a result, we present a way to teach and discuss the learning of metric relations in right triangles using a grid without using triangle similarity to deduce formulas.